Pharmacogenomics: Knowledge, Attitude and Practice among Future Doctors and Pharmacists-A Pilot Study - Adamu Yau, Mainul Haque (Journal of Applied Pharmaceutical Science, 2016)
Rational application of genomics into practice would lead to safer chemotherapy through individualized medicine. The increasing trends of genetic discoveries coupled with increased adoption of pharmacogenomics in developed countries pose challenges to the presence and future healthcare professionals, not only in Malaysia. This research, aimed to assess knowledge, attitude and practice of final-year future healthcare professionals towards pharmacogenomics. A cross-sectional study was conducted by administering self-completed questionnaire (Reliability 0.82) to 247 participants, among which 68.4% responded. More than half were female medical students. The mean knowledge scores in percentage were 57.57±20.2 with a significant difference between the two groups (p = 0.002). Positive attitude, but low practice were observed which differs between pharmacy and medical students, p
Keywords: Pharmacogenomics, future healthcare professionals, KAP.